2022
DOI: 10.48550/arxiv.2201.07810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The half mass radius of MaNGA galaxies: Effect of IMF gradients

Abstract: Gradients in the stellar populations of galaxies -e.g., in age, metallicity, IMF -can result in gradients in the stellar mass to light ratio, M * /L. Such gradients imply that the distribution of the stellar mass and light are different. For old stellar populations, such as those typical of early-type galaxies at z ∼ 0, the M * /L gradients are weak if driven by variations in age and metallicity. However, if they are driven by variations in the stellar Initial Mass Function (IMF), then they can be significantl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Many quiescent, massive galaxies are either extremely flattened (lenticular) or significantly rotationally supported (fast-rotators; Cappellari et al 2011). We refer back to the the mass-weighted size-mass relation for S0 and fast-rotating galaxies from the MANGA survey (Bernardi et al 2022), as shown in Fig. 4a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many quiescent, massive galaxies are either extremely flattened (lenticular) or significantly rotationally supported (fast-rotators; Cappellari et al 2011). We refer back to the the mass-weighted size-mass relation for S0 and fast-rotating galaxies from the MANGA survey (Bernardi et al 2022), as shown in Fig. 4a.…”
Section: Discussionmentioning
confidence: 99%
“…The grey points show the F444W sizes from Suess et al (2022a) for 1.0 < z < 2.5 galaxies at M * > 10 9 M , and the red symbols show UFOs. To guide the eye, the black lines show the relationship between half-mass radius and stellar mass at z ∼ 2(Suess et al 2019), and the blue lines show the size-mass relation for S0s and fast rotators fromBernardi et al (2022). Center: distribution of observed axis ratios and example population models with various intrinsic 3D shapes.…”
mentioning
confidence: 99%
“…The choice of the quantity of mock galaxies to be used for each object was taken as a good compromise between computational time and accuracy of the result. (Bernardi et al 2022) recently showed that a gradient in stellar population can reflect a gradient in the stellar mass-to-light (M/L) ratio within a galaxy, consequently affecting the 𝐵/𝑇. However, since we decide to use a constant IMF, the M/L is expected to be constant within a galaxy.…”
Section: Stellar Population Analysis and Rest-frame Colorsmentioning
confidence: 99%
“…However, these empirical structural measurements are fundamentally limited by the fact that even the longest wavelengths observed by HST (1.6 μm) correspond to restframe optical light at z ∼ 2, and shift into the rest-frame ultraviolet at higher redshifts. Local galaxies are known to exhibit radial gradients in their mass-to-light (M/L) ratios caused by gradients in their stellar ages, metallicities, or dust attenuation (e.g., Saglia et al 2000;La Barbera et al 2005;Tortora et al 2010;Greene et al 2015;Woo & Ellison 2019;Bernardi et al 2022). If these M/L gradients also exist at earlier time, then light-weighted size measurements at z ∼ 2 could differ significantly from mass-weighted sizes.…”
Section: Introductionmentioning
confidence: 99%